2018
DOI: 10.1021/acssuschemeng.8b01978
|View full text |Cite
|
Sign up to set email alerts
|

FeCo2S4 Nanosheet Arrays Supported on Ni Foam: An Efficient and Durable Bifunctional Electrocatalyst for Overall Water-Splitting

Abstract: Efficient and stable bifunctional electrocatalysts composed of Earth-abundant elements are crucial to the oxygen evolution reaction (OER) and the hydrogen evolution reaction (HER). Herein, FeCo 2 S 4 nanosheet arrays loaded on Ni foam (NF) are synthesized and first employed as a bifunctional electrocatalyst for full water-splitting. Remarkably, the self-assembled, binder-free, and cost-effective FeCo 2 S 4 /NF electrode shows high OER catalytic activity, which only requires an overpotential of 270 and 290 mV t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
29
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 91 publications
(34 citation statements)
references
References 59 publications
(122 reference statements)
2
29
0
Order By: Relevance
“…Inc. of Co/Ni-CW and reported bifunctional catalysts. [45][46][47][48][49][50][51][52][53][54][55][56][57] www.afm-journal.de www.advancedsciencenews.com 2010951 (8 of 10) S19, Supporting Information). [45][46][47][48][49][50][51][52] Moreover, the Co/Ni-CW electrode exhibits appropriate stability with ≈20% current density loss under the current density of 10 mA cm -2 for 48 h (Figure 5c).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Inc. of Co/Ni-CW and reported bifunctional catalysts. [45][46][47][48][49][50][51][52][53][54][55][56][57] www.afm-journal.de www.advancedsciencenews.com 2010951 (8 of 10) S19, Supporting Information). [45][46][47][48][49][50][51][52] Moreover, the Co/Ni-CW electrode exhibits appropriate stability with ≈20% current density loss under the current density of 10 mA cm -2 for 48 h (Figure 5c).…”
Section: Resultsmentioning
confidence: 99%
“…f) Comparison of cell voltages at a current density of 10 mA cm-2 and the substrate materials costs found in Amazon. Inc. of Co/Ni-CW and reported bifunctional catalysts [45][46][47][48][49][50][51][52][53][54][55][56][57].…”
mentioning
confidence: 99%
“…Studies have shown that Co/Ni based materials exhibited high electrocatalytic OER activity in alkaline solutions . These materials included cobalt (nickel) oxides/hydroxide, Co(Ni)Fe layered double hydroxides (LDHs), cobalt (nickel) molybdate, cobalt (nickel) sulfides, cobalt (nickel) selenides, cobalt (nickel) nitrides, and cobalt (nickel) phosphides . However, due to the low active surface area and the poor electrical conductivity, the performance of these electrocatalysts still does not meet the requirements for practical applications.…”
Section: Introductionmentioning
confidence: 99%
“…For overall water splitting in 1.0 M KOH, Lin et al . have observed that Ni 3 S 2 −Co 9 S 8 nano array on Ni foam exhibits enhanced activity (1.55 V at 10 mA cm −2 ) and stability (12 h), while Hu et al . have observed that FeCo 2 S 4 nanosheet array on Ni foam exhibits enhanced activity (1.56 V at 10 mA cm −2 ) and stability (20 h), and Li et al .…”
Section: Constructing Earth‐abundant 3d Nanoarrays For Efficient Overmentioning
confidence: 99%